The The Uncounted Dimension of Women in the Crab Meat Industry: Their Roles to Household Food Security - Lamela, Renee A. (Future Science / FSH-PH Publications, 2022)
The crab meat-picking industry has been recognized over the years worldwide. In this economy, women are well known as crab-pickers. They played crucial roles and faced a lot of challenges, yet their efforts to improve household food security are invisible and unrecognized. Hence, the study focused on the roles of women in the crab meat industry and their contributions to household food security and income in the Province of Masbate, Philippines. Through descriptive surveys and interviews, it was revealed that the majority of crab pickers are women with basic levels of educational attainment. Sixty-one to seventy percent (61%-70%) of the respondents rely solely on their household income for crab picking. Utilizing in-depth interviews, it was found out that respondents experienced crab-picking health-related problems, discrimination in recruitment, and staggering low wages. Therefore, even with the working conditions experienced by women, they greatly contribute to household income and food security in the area. It was deemed necessary to give emphasis to addressing challenges met by women through regular sanitary inspections by the authorities, revisiting recruitment policies in the industry, and imposing a minimum wage law to ensure that women contribute to and sustain household income.